2020
DOI: 10.1002/mpr.1865
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Gambling Disorder Identification Test: Results from an international Delphi and consensus process

Abstract: Objectives: Diverse instruments are used to measure problem gambling and Gambling Disorder intervention outcomes. The 2004 Banff consensus agreement proposed necessary features for reporting gambling treatment efficacy. To address the challenge of including these features in a single instrument, a process was initiated to develop the Gambling Disorder Identification Test (GDIT), as an instrument analogous to the Alcohol Use Disorders Identification Test and the Drug Use Disorders Identification Test.Methods: G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…This method is widely used in the health sciences and is regarded as the most rigorous method for determining group consensus. [23][24][25] In the gambling field, Delphi studies have been reported on: screening tests; 26 counsellor competencies; 27 and how friends, family, or members of the public can recognise and support someone with gambling problems, 28 but there has been no consensus study on effective measures for a public health approach. Accordingly, we aimed to determine evidence for consensus among an independent group of experts on effective measures that have potential for successful implementation in England.…”
Section: Introductionmentioning
confidence: 99%
“…This method is widely used in the health sciences and is regarded as the most rigorous method for determining group consensus. [23][24][25] In the gambling field, Delphi studies have been reported on: screening tests; 26 counsellor competencies; 27 and how friends, family, or members of the public can recognise and support someone with gambling problems, 28 but there has been no consensus study on effective measures for a public health approach. Accordingly, we aimed to determine evidence for consensus among an independent group of experts on effective measures that have potential for successful implementation in England.…”
Section: Introductionmentioning
confidence: 99%
“…In the GDIT item selection (Molander et al, 2019), it became evident that many items from previous gambling instruments assessed gambling-related school, work, and relationships problems lumped together in single items, equivalent to current and previous DSM diagnostic criteria (American Psychiatric Association, 1994. This particular double-and triple-barreled phrasing issue was also observed in the Delphi process (Molander et al, 2020) and was later adjusted, during the consensus meetings, into two GDIT items, assessing relationship problems in one item (GDIT Item 13 ), and gambling-related school or work problems in another (GDIT Item 14 ). Although the BCA (Walker et al, 2006) recommends that gambling-related problems concerning employment and productivity should be measured as a single feature in gambling instruments, most psychometric studies have evaluated gambling-related problems regarding work and/or relationships combined (i.e., in single items using double-barreled phrasing).…”
Section: Discussionmentioning
confidence: 99%
“…The GDIT was developed in a recent international Delphi and consensus process, aiming to establish a comprehensive measure which corresponded to a previous international research agreement regarding features of gambling outcome measures, known as the Note. GDIT = the gambling disorder identification test (Molander et al, 2019(Molander et al, , 2020; CFA = confirmatory factor analysis, using the weighted least square mean and variance adjusted estimator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations